A Rare Presentation of Recurrent Diverticulitis in a Patient with Ulcerative Colitis - Carlos Perez Hernandez; Sherif Elkattawy; Islam Younes; Paul Fanous; Daphne Gonzalez Aponte; Omar Makanay; Arun Naik (European Journal of Case Reports in Internal Medicine, 2022)
Diverticulitis and ulcerative colitis (UC) are two separate colonic pathologies with different underlying mechanisms. Diverticulosis involves herniation of mucosal and submucosal tissue through muscular tissue in response to increased intraluminal pressure. In contrast, it is believed that the muscular tone in patients with UC is reduced due to chronic inflammatory changes. Thus, it has been reported that there may be an inverse relationship between the presence of diverticulosis in patients with UC, in that UC may possibly be protective against developing diverticular disease. Consequently, the co-presence of both pathologies is uncommon. Here we present a case in which a woman with a history of UC and recurrent diverticulitis after elective partial colectomy was admitted for recurrent acute diverticulitis. It is quite challenging to diagnose diverticulitis in ulcerative colitis patients given the usually similar presentation with abdominal pain, diarrhoea and hematochezia. A level of high suspicion is required for diagnosis.